UJI KESESUAIAN EMPAT ISOLAT TRICHODERMA SPP. DAN DAYA HAMBAT IN VITRO TERHADAP BEBERAPA PATOGEN TANAMAN - Loekas Soesanto; Endang Mugiastuti; Ruth Feti Rahayuniati; Ratna Stia Dewi (Universitas Lampung, 2013)
Compatibility test of four Trichoderma spp. Isolates and in vitro inhibition ability on several plant pathogens. In vitro descriptive compatibility research was carried out to know the compatibility among Trichoderma spp. isolates and their inhibition ability toward several plant pathogens. Four Trichoderma spp. isolates used were ginger, shallot, banana, and pineapple isolates; while the pathogens used were pathogenic fungi (Fusarium, Colletotrichum, Phytophthora, and Sclerotium), bacteria (Ralstonia), and nematode (Meloidogyne dan Globodera). Observation was done toward inhibition zone between Trichoderma spp. isolates, colony radial growth, mycelial dry weight, and nematode mortality. Result of the research indicated that the four Trichoderma spp. isolates were compatible and no growth inhibition was observed. The inhibition ability of all Trichoderma spp. isolates varied and the ginger isolate had the highest inhibition ability and mortality on all fungal species and the nematodes, while on the pathogenic bacteria there was no inhibition.